2020
DOI: 10.1016/j.heliyon.2020.e05521
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study of human rabies cases in Bangladesh through verbal autopsy

Abstract: Identification of risk factors is crucial to find ways to reduce rabies deaths. We investigated the hospital records of rabies deceased through contact tracing of the relatives of the victims using enhanced verbal autopsies (VA) to identify why the people had to die from rabies in recent years in Bangladesh. Patients whose deaths were confirmed by physicians based on the history of animal exposure and clinical signs were taken into account for VA. Socio-demographic profile of the deceased, animal exposure, nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…Dogs are mainly responsible for causing rabies. This is well-reported and known worldwide, including in Bangladesh [ 19 , [35] , [36] , [37] , [38] ]. This study found that over 95% of the respondents from all populations possessed a high awareness about the transmission of rabies from dogs; however, there was a substantial gap regarding rabies transmission dynamics through domestic and wild animals.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Dogs are mainly responsible for causing rabies. This is well-reported and known worldwide, including in Bangladesh [ 19 , [35] , [36] , [37] , [38] ]. This study found that over 95% of the respondents from all populations possessed a high awareness about the transmission of rabies from dogs; however, there was a substantial gap regarding rabies transmission dynamics through domestic and wild animals.…”
Section: Discussionmentioning
confidence: 83%
“…Vaccinating at least 70% dogs in three consecutive years through MDV could attain a significant reduction in the virus transmission [ 47 , 48 ]. Regarding health-seeking behaviours of dog bite victims, recent studies showed that rabies victims sought treatment from by traditional healers (66.8%) instead of visiting hospital and receiving PEP which is the reflection of lack of formal education on rabies at the community level in Bangladesh [ 19 , 38 ]. Through increasing community level education, knowledge about dog bites and its consequences, and especially necessity of taking PEP measures to reduce the risk of becoming rabies infection can be improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a retrospective study spanning 12 years, Ghosh et al (2020) found 78% of 422 dog bites victims died after only receiving treatment by a traditional healer [ 14 ]. Another retrospective study in Bangladesh stated that 66.8% of 256 dog bite victims died after receiving treatment from a traditional healer [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, traditional healers were trained to refer patients for PEP at animal bite treatment centers [ 24 ]. Many KAP and retrospective studies included in this literature review emphasized the need for awareness of rabies prevention and PEP in the respective communities [ 14 , 41 , 43 , 46 , 49 ].…”
Section: Discussionmentioning
confidence: 99%